Evaluation of Root Canal Diameters and Radicular Wall Thickness of the Human Primary Molars by using Multidetector Computed Tomography: A Cross-sectional Study - Piyali Datta; Shabnam Zahir; Kaushik Dutta; Pratik Kumar Lahiri; Sudipta Kar; Biswaroop Chandra; Trishik Basak; Shreya Tripathi (Journal of Clinical and Diagnostic Research)
Introduction: Paediatric endodontics is critical for preserving the primary tooth until its physiologic exfoliation and ensuring the child’s quality of life. Endodontic treatment of human primary molars with varying internal geometry of the root canal necessitates extensive knowledge and skills. Aim: To evaluate the diameters of the root canals and the radicular wall thickness of human primary molars using Multidetector Computed Tomography (MDCT). Materials and Methods: This cross-sectional study study was performed in the Department of Paediatric and Preventive Dentistry in collaboration with the Department of Oral and Maxillofacial Surgery, Department of Antaomy of Guru Nanak Institute, Kolkata, West Bengal,India on selected 64 human primary maxillary and mandibular molars through inclusion and exclusion criteria and grouped them (Group 1, maxillary 1st molars; Group 2, maxillary 2nd molars; Group 3, mandibular 1st molars; and Group 4, mandibular 2nd molars). After proper sterilisation, the teeth were mounted on a wax platform, and the mounted teeth block was scanned by a computed tomography scanner. Analysis of these Computed Tomography (CT) scan images was done through Denta Scan (GE Healthcare, USA) software. In each of the corresponding cross-sections, the diameters of the root and the root canals were measured at their greatest diameter. The radicular wall thickness of the roots was derived by subtracting the measured diameter of the root canals from that of the roots in their respective cross-sections. Descriptive statistical analysis (Student’s t-test) was performed. A p-value less than equal to 0.05 was considered statistically significant. Results: The maximum mean diameter of the canal was found in the mesiobuccal root canal of both primary mandibular first molars (1.16±0.22 mm at cervical third) and second molars (1.12±0.16 mm at cervical third); and the minimum diameter was found in the distolingual root canal of both primary mandibular first molars (0.87±0.12 mm at cervical third) and second molars (0.89±0.16 mm at cervical third). The mean radicular wall thickness of the roots gradually increased from the apical third to the cervical third of both primary molars. Conclusion: The maximum root canal diameter and radicular wall thickness were found in the cervical third of the palatal root of maxillary second molars. The study evaluates the mean maximum and minimum diameters of each canal of human primary molars and radicular wall thickness in different cross-sections, which enables paediatric dental practitioners to establish effective paediatric endodontic treatment.